Comparison of stethoscope bell and diaphragm, and of stethoscope tube length, for clinical blood pressure measurement. Issue 3 (June 2016) - Liu, Chengyu; Griffiths, Clive; Murray, Alan; Zheng, Dingchang
Abstract : Objective: This study investigated the effect of stethoscope side and tube length on auscultatory blood pressure (BP) measurement. Methods: Thirty-two healthy participants were studied. For each participant, four measurements with different combinations of stethoscope characteristics (bell or diaphragm side, standard or short tube length) were each recorded at two repeat sessions, and eight Korotkoff sound recordings were played twice on separate days to one experienced listener to determine the systolic and diastolic BPs (SBP and DBP). Analysis of variance was carried out to study the measurement repeatability between the two repeat sessions and between the two BP determinations on separate days, as well as the effects of stethoscope side and tube length. Results: There was no significant paired difference between the repeat sessions and between the repeat determinations for both SBP and DBP (all P -values>0.10, except the repeat session for SBP using short tube and diaphragm). The key result was that there was a small but significantly higher DBP on using the bell in comparison with the diaphragm (0.66 mmHg, P =0.007), and a significantly higher SBP on using the short tube in comparison with the standard length (0.77 mmHg, P =0.008). Conclusion: This study shows that stethoscope characteristics have only a small, although statistically significant, influence on clinical BP measurement. Although this helps understand the measurement technique and resolves questions in the published literature, the influence is not clinically significant.